2011
DOI: 10.1016/j.neuropharm.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The CB2 cannabinoid receptor-selective agonist O-3223 reduces pain and inflammation without apparent cannabinoid behavioral effects

Abstract: Summary Although Δ9-tetrahydrocannabinol (THC) and other mixed CB1/CB2 receptor agonists are well established to elicit antinociceptive effects, their psychomimetic actions and potential for abuse have dampened enthusiasm for their therapeutic development. Conversely, CB2 receptor-selective agonists have been shown to reduce pain and inflammation, without eliciting apparent cannabinoid behavioral effects. In the present study, we developed a novel ethyl sulfonamide THC analog, O-3223, and compared its pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 40 publications
2
83
0
3
Order By: Relevance
“…These authors further demonstrated that activation of CB2 not only prevented, but also reversed, inflammation-induced edema (60). In other studies, treatment with a selective CB2 agonist reduced arachidonic acid-induced edema in the ear (31), and edema of hind paw elicited by intraplantar injection of lipopolysaccharide (38). These studies clearly support the antiinflammatory effects of CB2, although the precise mechanisms underlying CB2 activation-induced inhibition of inflammation remain to be clarified.…”
Section: Discussionmentioning
confidence: 69%
“…These authors further demonstrated that activation of CB2 not only prevented, but also reversed, inflammation-induced edema (60). In other studies, treatment with a selective CB2 agonist reduced arachidonic acid-induced edema in the ear (31), and edema of hind paw elicited by intraplantar injection of lipopolysaccharide (38). These studies clearly support the antiinflammatory effects of CB2, although the precise mechanisms underlying CB2 activation-induced inhibition of inflammation remain to be clarified.…”
Section: Discussionmentioning
confidence: 69%
“…1,1719 Pretreatment with selective CB2 agonists attenuated carrageenan induced edema in the hind paw of rats and the inhibitory effects were reversed by selective CB2 antagonists. 1 Similar treatments also decreased arachidonic acid induced edema in the ear 18 and edema of the hind paw elicited by intra-plantar injection of lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, chronic CP55,940, at a dose that produced CB 2 -mediated antiallodynic efficacy, failed to decrease body temperature in CB 1 KO mice, documenting that prolonged activation of CB 2 receptors does not result in hypothermia (Malan et al, 2001;Valenzano et al, 2005;Yao et al, 2009;Elliott et al, 2011;Kinsey et al, 2011;Amenta et al, 2012). Chronic CP55,940-treated WT, but not CB 1 KO mice, showed profound withdrawal signs when challenged with the CB 1 antagonist rimonabant, suggesting precipitation at CB 1 receptors produces withdrawal symptoms (Tsou et al, 1995;Aceto et al, 1996;Cook et al, 1998;Rubino et al, 1998;Lichtman et al, 2001).…”
mentioning
confidence: 98%